Strategic approach selection for public health through evidenced analytical tools - Gumashta, Raghvendra (International Journal Of Community Medicine And Public Health, 2017)
Background: The multi-dimensional perspectives of evidence based public health strategic approaches necessitates use of efficient analytical tools towards decision making for project and programmatic interventions on a larger framework of policy, behavior and resource utilization. Methods: Respondent driven sampling (RDS) was obtained through discussion, interview and participation in the status assessment questionnaire devised for the study. Results: Lack of new initiatives supported by non-dissemination of findings of research (75%), difficult logistics management (67.39%), unaddressed training needs (46.67%), lessons learnt remaining untransformed into actionable inputs (82.60%) and less emphasis on monitoring cum evaluation (44.56%) is observed respectively while assessing quality adherence, program design, vision statement and choices of public health approaches. Conclusions: ‘Comprehensive Management and Monitoring Approach’ is found to be the best public health approach for project design, formulation, plan extension, implementation, monitoring, evaluation and revision thereby necessitating targeted interventions through well managed technical cum financial inputs.